2022
DOI: 10.1021/acsomega.2c06237
|View full text |Cite
|
Sign up to set email alerts
|

Retention Improvement of HZO-Based Ferroelectric Capacitors with TiO2 Insets

Abstract: The influence of the bottom TiO 2 interfacial layer grown by atomic layer deposition on the ferroelectric properties of the TiN/ Hf 0.5 Zr 0.5 O 2 /TiN capacitors is systematically investigated. We show that the integration of the TiO 2 layer leads to an increase in the polar orthorhombic phase content in the Hf 0.5 Zr 0.5 O 2 film. In addition, the crystalline structure of the Hf 0.5 Zr 0.5 O 2 film is highly dependent on the thickness of the TiO 2 inset, with monoclinic phase stabilization after the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…[ 58 ] In the case of sample TiN/HZO/W, STEM‐EELS data revealed the presence of an interfacial layer at TiN/HZO bottom interface, due to oxygen scavenging. [ 26,63,64 ] However, we concluded that both in‐plane strain from W TE and a thin dead‐layer at the HZO/W top interface were the key factors that notably improved the ferroelectric properties of samples TiN/HZO/W and W/HZO/W, where an extremely high value of switchable polarization was reached.…”
Section: Discussionmentioning
confidence: 92%
“…[ 58 ] In the case of sample TiN/HZO/W, STEM‐EELS data revealed the presence of an interfacial layer at TiN/HZO bottom interface, due to oxygen scavenging. [ 26,63,64 ] However, we concluded that both in‐plane strain from W TE and a thin dead‐layer at the HZO/W top interface were the key factors that notably improved the ferroelectric properties of samples TiN/HZO/W and W/HZO/W, where an extremely high value of switchable polarization was reached.…”
Section: Discussionmentioning
confidence: 92%
“…[11] However, its low remnant polarization intensity and high annealing temperature have restricted its further development. [12] In order to improve the remanent polarization intensity of Hf-based ferroelectric materials, researchers generally insert an interface layer between the electrode and the ferroelectric layer, such as TiO 2 , [13,14] Al 2 O 3 , [15,16,17] HfO 2 , [18] ZrO 2 , [19,20] La 2 O 3 , [21] CeO x , [22] etc. Among them, there are reported works on the performance improvement of ZrO 2 layer in memory [23][24][25] and ZrO 2 has good lattice matching effect with HfO 2 , which was suitable as insert layer for improving performances of Hf-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…The peak observed at 30.5° corresponds to the FE O -phase and T -phase denoted as (111) o /(101) t in the HZO material. This peak is an important indicator of the structural composition of the HZO, indicating the coexistence of FE O -phase, referred to as (111) o , and non-FE T -phase, referred to as (101) t . , The observed downward shift in the 2θ angle indicates the presence of tensile strain in the O -phase of the HZO thin film, which is conducive to the formation of the O -phase. Note that an upward peak shift would indicate the presence of compressive strain .…”
Section: Resultsmentioning
confidence: 99%